2011
DOI: 10.1371/journal.pone.0017239
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological Study of Concomitant Use of Chinese Medicine and Antipsychotics in Schizophrenic Patients: Implication for Herb-Drug Interaction

Abstract: BackgroundHerb-drug interactions are an important issue in drug safety and clinical practice. The aim of this epidemiological study was to characterize associations of clinical outcomes with concomitant herbal and antipsychotic use in patients with schizophrenia.Methods and FindingsIn this retrospective, cross-sectional study, 1795 patients with schizophrenia who were randomly selected from 17 psychiatric hospitals in China were interviewed face-to-face using a structured questionnaire. Association analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…Our epidemiological study has shown that CLZ is often concomitantly used with herbal medicine, which may result in adverse clinical outcomes (Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Our epidemiological study has shown that CLZ is often concomitantly used with herbal medicine, which may result in adverse clinical outcomes (Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…With an increasing use of herbal medicine in managing psychiatric disease, herb-drug interactions have become an important issue in clinical practice (Zhang et al, 2010(Zhang et al, , 2011. This is particularly apparent in China where herbal medicine has become an important therapeutic approach to psychiatric disorders (Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it was reported that 33.4% of patients using antipsychotics also took traditional Chinese medicine concurrently; 7.2% of these patients had worse outcomes compared to 4.4% of those using antipsychotics alone. 45 Risperidone is metabolized and can contribute to numerous drug interactions because it is metabolized by CYP3A4, the most common drug-metabolizing enzyme. 46 Many children have GI problems 47 and are given numerous medications that change the GI flora.…”
Section: Metabolismmentioning
confidence: 99%